Regulation data for the horizontal jump of children and adolescents - Rossana Gomez-Campos; Ruben Vidal-Espinoza; Luis Felipe Castelli Correia de Campos; Cynthia Lee Andruske; Jose Sulla-Torres; Camilo Urra-Albornoz; Wilbert Cossio-Bolaños; Fernando Alvear-Vasquez; Jorge Mendez-Cornejo; Marco Cossio-Bolaños (PAGEPress Publications, 2021)
The Horizontal Jump (HJ) is a daily tool that could be used to categorize the level of muscle fitness performance of the lower limbs. The goal was to compare the muscle fitness with those of international studies and to propose percentiles to assess the HJ performance of children and adolescents. A cross-sectional study was conducted. A total number of 3023 children and adolescents between the ages of 6.0 to 17.9 were studied. Weight, height, waist circumference (WC), and lower limb muscle fitness were evaluated. The student HJ performance values in Chile were inferior when compared to HJ performance in Brazil, Poland and Europe. For the Greek study, differences occurred only from age 6 to 15 years old. In comparison to Colombia, students showed better muscle fitness performance. These differences appeared in childhood and lasted until the beginning of adolescence. Percentiles were created to assess the lower limb fitness being an easy tool to be used and applied to classify lower limb strength.